Religion (Islam) and International Relations: A Perspective - Sahrasad, Herdi (UIN ALAUDDIN MAKASSAR, 2023)
This article argues that religion (Islam) and international relations in the era of post-war globalization, have its own relevance and contextuality. So far, the international relations in the post-Cold War was marked by the rise of actors and issues. In the realm of actors, emerging non-state actors who perform various international relations practices both leading to cooperation and peace as well as toward conflict and conflict. The state is no longer a dominant actor although it remains the primary actor. In the realm of the issue, the concern of mankind is no longer focused on high politics in the form of matters of national security and military alone, but the issues that were originally included in the category of low politics were even more prominent. As an impact, disruption to international security and order is not a monopoly of the issue of national security. Non-traditional security threats such as environmental issues, the spread of disease, transnational crime and others, also threaten global peace. Conflicts of communal identity that are usually based on religion, ethnicity, race, clan, tribe, or other identity become one of the leading ones. And in such international situation, Islam is challenged to respond the complexities of today's international problems.